Development of Character Education Development through the Scout Movement - Ika Putra Viratama (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2023)
This study describes the development of character building through supervision in the form of supervision. This research is motivated by the many deviations that occur in society. This deviation shows the decline of the national character. MA Darul Ma'arif Numbay implements the development of character education through the scout movement. The purpose of this study was to obtain an overview of the design, implementation and consequences of character education through the MA Darul Ma'arif scouting activities. The research method is a case study using triangulation techniques to obtain data, namely. observation techniques, interviews and document analysis. The data analysis used was pre-field data analysis and data analysis during the field, namely. H. Data reduction, presentation and conclusion. Based on this research, scouting can be an alternative in character building.